A taxonomic study of the genus Paralaevicephalus Ishihara (Hemiptera: Cicadellidae: Deltocephalinae) , with description of four new species from China - Xing, Jichun; Dai, Renhuai; Li, Zizhong (Zootaxa, 2009)
The paper deals with eight species of the genus Paralaevicephalus Ishihara, 1953 (Hemiptera: Cicadellidae: Deltocephalinae) from China, including four new species, Paralaevicephalus huaxiensis sp. nov. , Paralaevicephalus angustus sp. nov., Paralaevicephalus grossusus sp. nov. and Paralaevicephalus lamellatus sp. nov.. A key is given to distinguish all species of the genus, and illustrations of genitalia are provided. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University (IEGU).